Phase Risk Analysis of Overhead Lines Under Complex Icing Conditions - Xinsheng Dong; Yuanhao Wan; Yiran Zhang; Yongcan Zhu (Applied Sciences)
Phase-to-ground discharge of transmission lines due to ice cover is a common issue. To assess the risk of phase-to-ground discharge of overhead lines under complex ice-covering conditions, this study used finite element analysis to model the interaction between ground wire, conductor, and insulator. The study examined how different factors affect the minimum safe distance between the conductor and ground wire, as well as the risk coefficient of phase-to-ground discharge and the risk zone. The finding reveals that as icing thickness increases, conductor bouncing intensifies, reducing the phase-to-ground distance, and placing one half of the line span within the risk zone for the given conditions. For the same length of de-icing, the closer the de-icing region is to the midpoint, the greater is the maximum jump height of the conductor. When the span is extended to 600 m, the risk range covers approximately 70% of the total line length. Under strong winds, conductor lateral displacement increases with wind speed, which leads to a higher risk of discharge.